If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 9 = 3 + -6x Reorder the terms: 9 + -10x = 3 + -6x Solving 9 + -10x = 3 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 9 + -10x + 6x = 3 + -6x + 6x Combine like terms: -10x + 6x = -4x 9 + -4x = 3 + -6x + 6x Combine like terms: -6x + 6x = 0 9 + -4x = 3 + 0 9 + -4x = 3 Add '-9' to each side of the equation. 9 + -9 + -4x = 3 + -9 Combine like terms: 9 + -9 = 0 0 + -4x = 3 + -9 -4x = 3 + -9 Combine like terms: 3 + -9 = -6 -4x = -6 Divide each side by '-4'. x = 1.5 Simplifying x = 1.5
| 3a+-a= | | -2+3x=x-2 | | X^2-7x-4=9 | | +17c=-34 | | 5x^2-125= | | 69(x-18)=9x | | 8c+15=-19-9c | | x*8+22=x*5+82 | | 3=5y+13 | | 3x-8=-20-x | | 5m-7=-12 | | ln(2x+5)=2.3 | | 2x^2+9=59 | | f(x)=(X^2-4)-5 | | 2x-2x=4-2x | | 2k^2-2/7k-7 | | 3n-10=-3 | | 14x=-29 | | 3[5x-4(x+3)]+21=2(x-17) | | 3x-15=6x+1 | | 19x^2-18=0 | | -4-3y=-7 | | 90m+12n-5m+3n+95= | | 100/150=x/230 | | (2x-8)(5x+2x)=0 | | 2*(-2)-3(-1)=-7 | | 2*(-2)-3(-1)= | | 135=9x | | 18a^3+24a^2+8a=0 | | (3w-5)/5=(2w+4)/7 | | 2(343x)+5=91 | | 3x-3=11+99 |